Implementation of IoT (Internet of Thing) in the Design of a Smart Robot Prototype for Automatic Waste Disposal Based on Arduino at Mega - Badriah Nursakinah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The background of this research is to design a prototype for an automatic waste disposal robot based on Arduino AT Mega which is integrated with IoT (Internet of Things). Where the Internet of Things can generally be interpreted as objects around us that can communicate with each other via the internet network. Internet Of Thing has the concept of expanding the benefits of being connected to a continuous internet connection. The aim of this research is to design a prototype for an automatic waste disposer that was developed by integrating with IoT technology. The input process is carried out as an integration process between the Arduino and the HC-SR04 sensor and the Infrared Line Tracking sensor. So that the Arduino and HCSR 04 and Line Tracking sensors can work optimally, the main thing to do is carry out the configuration process using a beardboard and jumper cables as well as LED lights to ensure whether the sensors and other supporting tools are integrated with the Arduino. Where in the integration process between the Arduino buit and the ESP8266 so that the movement of the prototype can be easily monitored only via a smartphone or laptop even remotely